Evaluation of accuracy of OraQuick® rapid test in detecting HIV antibodies in saliva of Nigerians (Nigerian Dental Journal, 2012)
Objective: The accuracy of OraQuick® rapid test in detecting HIV 1 & 2 antibodies in saliva is evaluated against the blood EIA benchmark tests with confirmatory testing, against which OraQuick® accuracy is determined.Method: Paired samples of saliva and blood from 281 Nigerians were tested for HIV antibodies, and compared for sensitivity and specificity. Subjects included in the study were  those who had a complete test, which included saliva test with OraQuick® rapid test, serologic test using conventional Enzyme Immunoassay (EIA), and confirmatory serological test.Result: From the 281 subjects who completed the oral fluid-based OraQuick® tests & EIA with confirmatory tests, 192 were seropositive and 89 seronegative for HIV 1 & 2 antibodies. The  sensitivity (95% CI) of OraQuick® was 98.96% (97.98% to 99.96%) and specificity was 100% thereby comparing favorably with serum EIA with benchmark sensitivity of 100% and specificity (95% CI) of 96.63% (95.61 to 97.56).Conclusion: Saliva based OraQuick® rapid assays for detecting HIV antibodies using oral fluids give accurate sensitivity and specificity results comparable to EIA results with serum samples. They are more acceptable, easier to use and not invasive.
Keywords: Oraquick; Saliva; HIV detection